Celecoxib-related gastroduodenal ulcer and cardiovascular events in a randomized trial for gastric cancer prevention - Feng, Guo-Shuang (The WJG Press and Baishideng, 2008)
AIM: To evaluate the long-term risk of gastroduodenal ulcer and cardiovascular events induced by celecoxib in a population-based, randomized, double-blind, placebo-controlled study. METHODS: From 2004 to 2006, a total of 1024 Chinese patients (aged 35 to 64 years) with severe chronic atrophic gastritis, intestinal metaplasia or dysplasia were randomly assigned to receive 200 mg of celecoxib twice daily or placebo in Linqu County (Shandong Province, China), a high-risk area of gastric cancer. All gastroduodenal ulcer and cardiovascular events occurred were recorded and the patients were followed up for 1.5 years after treatment. At the end of the trial, a systematic interview survey about other adverse events was conducted. RESULTS: Gastroduodenal ulcer was detected in 19 of 463 (3.72%) patients who received celecoxib and 17 of 473 (3.31%) patients who received placebo, respectively (odds ratio = 1.13, 95% CI = 0.58-2.19). Cardiovascular (CV) events occurred in 4 patients who received celecoxib and in 5 patients who received placebo, respectively. Compared with those who received placebo, patients who received celecoxib had no significant increase in occurrence of CV events (hazard ratio = 0.84, 95% CI = 0.23-3.15). Among the adverse events acquired by interview survey, only the frequency of bloating was significantly higher in patients treated with celecoxib than in those treated with placebo. CONCLUSION: Treatment of gastric cancer with celecoxib is not associated with increased risk of gastroduodenal ulcer and cardiovascular events.